TINJAUAN YURIDIS TERHADAP PROSES PENYELESAIAN SENGKETA KEPEGAWAIAN APARATUR SIPIL NEGARA DI PENGADILAN TATA USAHA NEGARA SAMARINDA - Krismanindika, Revita Martha (Journal of Law ( Jurnal Ilmu Hukum ), 2018)
ABSTRACTÂ Nowadays, there are many Indonesians who are busy wanting to become civil servants. Many things are considered by the community to become civil servants, such as a fairly good basic salary and then the benefits provided by the government both central and regional are quite a lot. With so many civil servants, there are many problems faced by the government itself, such as employment disputes, in the form of decisions issued by TUN officials / bodies.This research is a study of normative law that is legal research method that is done by researching library materials or secondary data only. The research procedure used is the research of collecting legal materials that will be used in this research is literature study is data collection by reading the legislation, official documents and literatures closely related to the issues discussed.The results of my research at Pengadilan Tata Usaha Negara Samarinda explained that the efforts that could be made were through administrative efforts by filing objections within the agency and with administrative appeals to the Civil Service Supervisory Agency (BAPEK), appeals were made after filing objections but were still not satisfied. Then if the administrative effort has been passed but is still not satisfied, then it can submit a claim to the State Administrative Court (PTUN). So it can be concluded, if there is a staffing contract, the civil servant can make legal efforts as stipulated in the Act.Â Keywords: Government Employees, Dispute, PTUN